Dynamic Changes Analysis of Land Resource Balance in North Maluku Province, Indonesia - Elya Pratiwi Isti Faroh; Fatih Cinderaswari Puspaningrani; Gema Reinadova; Muhammad Rais Akbar; Novanna Dwi Septyo Anggraeni; Oki Silvie Wildiyanti; Utia Kafafa; Ratih Fitria Putri (Universitas Gadjah Mada, 2020)
Land resources are part of nature related to the availability of water, nutrients, and food that are dynamic and play an important role in the lives of living creatures, including humans. From time to time, land use experiences changes in response to human activities that benefit their lives. This research was conducted to determine trends in land use change in North Maluku Province, Indonesia, as well as to find out the land resource balance and land carrying capacity in the province. The methods comprised a simple descriptive and quantitative analysis along with spatial analysis using GIS. The results showed that land use in North Maluku Province for paddy fields was higher than that for non-paddy land use. However, the increase in non-paddy land use was greater every year compared with the increase in paddy land use. The land resource balance in North Maluku Province in 2010–2018 also showed a decrease in non-agricultural protected forest, by 150,895.79 ha, as well as an increase in 4,286 ha of irrigated paddy fields. Meanwhile, the land carrying capacity during this same period was found to be declining at a rate of 6% per year, based on the population increase each year within a permanent land area.